Study of the Thoughts of Philosophical Figures - Amalia Nabila; Udin, Tamsik; Gusta, Andina (Bibliotheca: Journal of Philosophy, 2026)
This article examines the thoughts of several important figures in the philosophy of science through a literature review approach. The figures discussed include Plato, who emphasized the importance of the world of ideas as the ultimate truth; Aristotle, who developed an empiricism-based philosophy through formal logic (syllogism); and Francis Bacon, who emphasized the role of inductive methods, observation, and experimentation as the foundation for the development of science. Furthermore, this study also discusses the thoughts of Islamic philosophers, namely Al-Farabi, who successfully combined the ideas of Plato and Aristotle within the framework of Islamic thought; Ibn Sina, who developed the philosophy of existence through the concepts of wajib al-wujud and mumkin al-wujud; and Al-Ghazali, who played an important role in efforts to harmonize philosophy, theology, and Sufism. Through this study, it is hoped that a comprehensive understanding can be obtained regarding the contributions of these figures in the development of the philosophy of science and their relevance to scientific studies to the present day.